Marcovaldo, o sea, Las estaciones en la ciudad - Calvino, Italo (Biblioteca Calvino (Ediciones Siruela), 2012)
An unskilled worker in a drab northern Italian industrial city of the 1950s and 1960s, Marcovaldo has a practiced eye for spotting natural beauty and an unquenchable longing to come a little closer to the unspoiled world of his imagining. Much to the puzzlement of his wife, his children, his boss, and his neighbors, he chases his dreams, gives rein to his fantasies, tries-with more ingenuousness than skill-to lessen his burden and that of those around him. The results are never the anticipated ones.